Herb-drug interactions of silybinin and cilofexor in beagle dogs based on pharmacokinetics by UPLC-MS/MS - Wei, Xinyi; Su, Yanding; Cheng, Qian; Liang, Songmao; Zhang, Tingping; Duan, Lengxin; Shen, Xiuwei; Qiu, Xiangjun (Frontiers in Pharmacology, 2024)
A remarkably sensitive, accurate, and efficient ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) approach was developed as a facile and expeditious method for measuring cilofexor concentration in beagle dogs, the herb-drug interactions (HDIs) between silybinin and cilofexor was explored based on pharmacokinetics.The plasma sample protein of the beagles were rapidly sedimented with acetonitrile, and cilofexor and tropifexor (internal standard, ISTD) were separated by gradient elution using a 0.1% formic acid aqueous solution and acetonitrile as the mobile phase. The concentrations were detected using positive ion multiple reaction monitoring (MRM) mode. Mass transfer pairs were m/z 587.91→267.91 for cilofexor and m/z 604.08→228.03, respectively. A two-period self-controlled experimental design was adopted for the HDIs experiment. In the first period ( Group A), six beagle dogs were orally administered cilofexor at a dose of 1 mg/kg. In the second period ( Group B), silybinin (3 mg/kg) was orally administered to the six beagle dogs twice a day for seven consecutive days, after which cilofexor was orally administered. The cilofexor concentration in beagle dogs was determined, and HDIs were evaluated based on their pharmacokinetics.The accuracy and precision of cilofexor were both less than 15%, and the recoveries, matrix effects, and stability met the relevant requirements. The Cmax of cilofexor in group B was 49.62% higher than that in group A, whereas the AUC(0-t) and AUC(0−∞) of cilofexor in group B were 47.85% and 48.52% higher, respectively, than those in group A. Meanwhile, the t1/2 extended from 7.84 h to 9.45 h, CL and Vz decreased in Group B.Conclusions: A novel UPLC-MS/MS approach was successfully applied for the measurement of cilofexor in beagle dog plasma. Silybinin can alter the pharmacokinetics of cilofexor in beagle dogs, thereby increasing plasma exposure to cilofexor.